Effects of built environment on activity participation under different space-time constraints: A case study of Guangzhou, China. (January 2021) - Chen, Zifeng; Yeh, Anthony Gar-On
Highlights: Associations of built environment, activity and space–time constraint are explored. Effects of built environment on activities are influenced by space–time constraints. Built environment cannot affect the activities of residents with large constraints. Physical planning should take into account residents' unequal space–time constraints. Abstract: Conventional facility planning seeks to provide service facilities to meet population demand in an aggregate manner. However, recent studies reveal that the provision of facilities in residential neighborhoods does not necessarily mean easy service access for certain groups. This issue is approached through the lens of space–time constraints in this study, which asserts that because people with different socioeconomic attributes experience different space–time constraints, the effects of the same built environment on actual access can considerably vary. Based on the activity-diary data from 493 respondents in Guangzhou, China, this study conducts a quasi-experiment facilitated by the propensity score matching approach. Residents in low-density suburban areas and those in high-density central city areas are considered as the control and treatment groups, respectively. By comparing the activity-travel behavior between these two groups, this work presents an analysis of the effects of service density improvement on residents' actual service access. Moreover, the differences of such effects are examined through separate quasi-experiments for residents with the largest, medium and smallest space–time constraints. Residents who originally experience the smallest space–time constraints could further benefit from the enhancement of service density, whereas those who originally suffer from the largest and medium space–time constraints could not. These findings imply that conventional facility planning may not provide equitable outcomes. Therefore, facility planning and management should address and integrate residents' unequal experiences of space–time constraints into time-sensitive policies (e.g., flextime policies).